IMPLEMENTASI PENDIDIKAN KARAKTER TERHADAP PERILAKU SISWA DI SDN GUNUNG MELATI 1 KABUPATEN TANAH LAUT - Nadya Huda (Elementa: Jurnal Pendidikan Guru Sekolah Dasar, 2020)
The objectives of this study were (1) to determine the implementation of character education for students at SDN Gunung Melati 1, Tanah Laut Regency. (2) to determine the implementation of character education on student behavior at SDN Gunung Melati 1 Tanah Laut Regency. The research method used was quantitative methods, while the data mining tools were questionnaires and documentation. Data processing used simple linear regression equation formula. The conclusion that can be drawn is that the implementation of character education at SDN Gunung Melati 1 Tanah Laut Regency has been going well. The results of statistical analysis of simple linear regression calculations obtained N = 35 indicating the tcount value of 4.258 is greater than the tcount with a significant level of 5% indicating the number 2.03. Thus the alternative hypothesis (Ha) which says there is an effect of the implementation of character education on student behavior at SDN Gunung Melati 1 Tanah Laut Regency.